INVESTMENT COMPONENT OF THE STRATEGIC MANAGEMENT OF THE DEVELOPMENT OF ENTERPRISES IN THE INDUSTRIAL SECTOR OF UKRAINE (Development Service Industry Management, 2024)
The article substantiates the relevance of investment management in the context of rapidly changing economic realities, particularly under the influence of globalization, technological innovations, and internal challenges. In the context of military operations and crisis phenomena, effective investment management becomes a key factor for increasing competitiveness, modernizing production, and ensuring sustainable economic growth. The purpose of the article is to analyze and evaluate the activities of enterprises in the industrial sector of Ukraine and also to develop a methodological approach to ensure the investment component, which allows for identifying additional opportunities for attracting additional financial resources and optimizing them. It is proved that industry is the main driver of exports, which helps to increase foreign exchange earnings and strengthen the country's economic stability. The article emphasizes the importance of effective management of industrial enterprises, which ensures their sustainable development and competitiveness. Developing strategies that consider current economic challenges, optimizing resources, and introducing innovations are key aspects of this process. It is also noted that there has been a significant drop in the total number of enterprises in Ukraine, which requires urgent measures to support and restore them. A similar decline is observed in the number of operating industrial enterprises by type of economic activity (B + C + D + E).The study formulates a methodological approach to ensuring the investment component of industrial sector enterprises, which includes 8 main stages: analysis of needs and potential; strategic planning; creation of a favorable investment climate; state support and incentives; development of partnerships; attraction of foreign investment; financial accessibility; and performance evaluation.The results of the study will contribute to the development of industry and economic recovery, emphasizing the importance of strategic investment management in the current environment.
Keywords: industrial sector; enterprise; strategic management; development